Clinical Outcomes of Nerve Transfers in Peroneal Nerve Palsy: A Systematic Review and Meta-Analysis - Head, Linden K.; Hicks, Katie; Wolff, Gerald; Boyd, Kirsty U. (Journal of Reconstructive Microsurgery, 2019)
Background Given the unsatisfactory outcomes with traditional treatments, there is growing interest in nerve transfers to reestablish ankle dorsiflexion in peroneal nerve palsy. The objective of this work was to perform a systematic review and meta-analysis of the primary literature to assess the effectiveness of nerve transfer surgery in restoring ankle dorsiflexion in patients with peroneal nerve palsy.Methods Methodology was registered with PROSPERO, and PRISMA guidelines were followed. MEDLINE, EMBASE, and the Cochrane Library were systematically searched. English studies investigating outcomes of nerve transfers in peroneal nerve palsy were included. Two reviewers completed screening and extraction. Methodological quality was evaluated with Newcastle-Ottawa Scale.Results Literature search identified 108 unique articles. Following screening, 14 full-text articles were reviewed. Four retrospective case series met inclusion criteria for meta-analysis. Overall, 41 patients underwent nerve transfer for peroneal nerve palsy. The mean age of the patients was 36.1 years, mean time to surgery was 6.3 months, and the mean follow-up period was 19.0 months. Donor nerve was either tibial (n = 36) or superficial peroneal branches/fascicles (n = 5). Recipient nerve was either deep peroneal (n = 24) or tibialis anterior branch (n = 17). Postoperative ankle dorsiflexion strength demonstrated a bimodal distribution with a mean Medical Research Council of 2.1. There were no significant differences in dorsiflexion strength between injury sites (p = 0.491), injury mechanisms (p = 0.125), donor (p = 0.066), or recipient nerves (p = 0.496). There were no significant correlations between dorsiflexion strength and patient age (p = 0.094) or time to surgery (p = 0.493).Conclusions There is variability in dorsiflexion strength following nerve transfer in peroneal nerve palsy, whereby there appear to be responders and non-responders. Further studies are needed to better define appropriate patient selection and the role of nerve transfers in the management of peroneal nerve palsy.
Keywords: peripheral nerve; nerve transfer; peroneal nerve palsy